Nordic Walking training in BungyPump form improves cognitive functions and physical performance and induces changes in amino acids and kynurenine profiles in older adults - Rodziewicz-Flis, Ewa; Juhas, Ulana; Kortas, Jakub Antoni; Jaworska, Joanna; Bidzan-Bluma, Ilona; Babińska, Anna; Micielska, Katarzyna; Żychowska, Małgorzata; Lombardi, Giovanni; Antosiewicz, Jędrzej; Ziemann, Ewa (Frontiers in Endocrinology, 2023)
Although impacts of physical activity on cognitive functions have been intensively investigated, they are still far from being completely understood. The aim of this study was to evaluate the effect of 12 weeks of the Nordic Walking training with BungyPump resistance poles (NW-RSA) on the amino acid and kynurenine profiles as well as selected myokine/exerkine concentrations, which may modify the interface between physical and cognitive functions. A group of 32 older adults participated in the study. Before and after the intervention, body composition, cognitive functions and physical performance were assessed. Blood samples were taken before and 1h after the first and last session of the NW-RSA training, to determine circulating levels of exercise-induced proteins, i.e., brain-derived neurotrophic factor (BDNF), irisin, kynurenine (KYN), metabolites and amino acids. The NW-RSA training induced a significant improvement in cognitive functions and physical performance as well as a reduction in fat mass (p=0.05). Changes were accompanied by a decline in resting serum BDNF (p=0.02) and a slight reduction in irisin concentration (p=0.08). Still, changes in irisin concentration immediately after the NW-RSA intervention depended on shifts in kynurenineirisin dropped as kynurenine increased. The kynurenine-to-tryptophan and phenylalanine-to-tyrosine ratios decreased significantly, suggesting their possible involvement in the amelioration of cognitive functions. No changes of glucose homeostasis or lipid profile were found. Shifts in the concentrations of selected amino acids might have covered the increased energy demand in response to the NW-RSA training and contributed to an improvement of physical performance. Summing up, regular Nordic Walking training with additional resistance (BundyPump) improved cognitive functions and physical performance. These positive effects were associated with a reduced BDNF concentration and kynurenine-to-tryptophan ratio as well as changes in the amino acid profile.